2017
DOI: 10.1108/ijem-11-2015-0150
|View full text |Cite
|
Sign up to set email alerts
|

How leaders communicate their vulnerability: implications for trust building

Abstract: Purpose The notion of vulnerability underlies relationships of trust. Trust between leaders and staff is needed to solve concerns that hinder equity and excellence in teaching and learning. The purpose of this paper is to examine whether and how leaders show vulnerability by disclosing own possible contributions to concerns they try to resolve. Design/methodology/approach Data included transcripts of conversations held by 27 educational leaders about a concern with another staff and a questionnaire about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
0
26
0
6
Order By: Relevance
“…Trust in management is one of the main factors influencing employees' decision to share knowledge (Renzl 2008;Pervaiz 2016). Trust is a willingness to be vulnerable (Meyer et al 2017), and it is strongly associated with the belief that other people will not use this situation for their own benefit. Therefore, trust is a result of two contradicting interactions: on the one hand, there is a fear of losing one's own value; on the other hand, there is desire to collaborate.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust in management is one of the main factors influencing employees' decision to share knowledge (Renzl 2008;Pervaiz 2016). Trust is a willingness to be vulnerable (Meyer et al 2017), and it is strongly associated with the belief that other people will not use this situation for their own benefit. Therefore, trust is a result of two contradicting interactions: on the one hand, there is a fear of losing one's own value; on the other hand, there is desire to collaborate.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Trust can be interpreted as willingness to trust or depend on an individual or group. Moreover, an employee sharing knowledge must have trust that the management will see it and award him/her for it (Serenko et al 2016), may it be an individual or group award which, as a result, would improve group performance (Meyer et al 2017); therefore, trust in management can enhance knowledge sharing. According to Renzl (2008), trust also enables to concentrate personnel on the task to be carried out in order to create the added value for the organization.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…A superintendent that engages in open reflections with school leaders makes the school leaders open up as well. Meyer et al (2017) suggest that "those in power can relieve the tensions created by differential power relationships through specific behavioural practices that signal their trust-building motives" (p. 223). In contrast, when distrust emerge "the goal of communication often becomes the protection of one's interest and the reduction of one's anxiety rather than the accurate transmission of ideas" (Tschannen-Moran 2014, pp.…”
Section: Trustmentioning
confidence: 99%
“…Although empirical research on leader vulnerability is scant, available studies on leadership vulnerability and character tend to confirm the importance of vulnerability for integrity and character strength (Demirci, Ekşi, Ekşi & Kaya, 2019;Lopez, 2018). Leader vulnerability has been correlated with positive leadership characteristics such as charisma, emotional connection with followers, building trust and establishing psychological safety (Lopez, 2018;Mane, 2019;Meyer, Le Fevre & Robinson, 2017). Demirci et al (2019) found that several aspects of character strength correlate significantly with vulnerability.…”
Section: Integrity and The Adjunctive Virtuous Trait Of Vulnerabilitymentioning
confidence: 99%